Improving Activities and Learning Outcomes of Procedure Text Lesson Using Cooperative Learning Model with Jigsaw Technique in Junior High School - Hery Krisnanto (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2018)
The purpose of this study are: 1) to find out what is learning model for Reading Comprehension in Procedure Text for class IX C students of Adiwerna 5 State Junior High School Semester I Academic Year 2017/2018; 2) to determine whether cooperative learning model with jigsaw technique can improve Reading Comprehension learning outcomes Material Text Procedure for class IX C students of Adiwerna 5 State Junior High School Semester I Academic Year 2017/2018. This research was conducted for six months from July 2017 to December 2017. July and August 2017 are used to prepare proposals and preparations, September 2017 is used to carry out research, October, November 2017 to collect and analyze data, December 2017 to compile reports and seminars. The subjects of this study were students of class IX C of Adiwerna 5 State Junior High School in Tegal Regency, totaling 34 students with details of 16 men and 18 women. Implemented in 2 cycles, to increase the activity and learning outcomes of Reading Comprehension material Procedure Text by using cooperative learning model with jigsaw technique. Each cycle includes four stages which include the planning, implementation, observation and reflection stages. Based on the analysis of the results of observations and assessments conducted by researchers, it can be concluded that: 1) the results of the study in the pre-cycle reached the percentage of student activity of 38.23% in the first cycle and continued in the second cycle reached the average percentage of student activity by 76.48% , means there is an increase of 38.25%; 2) Learning outcomes of Reading Comprehension in Procedure Text also increases. This can be known as the posttest 1 and posttest 2 values that have been measured by the researcher with the classical learning completeness indicator in the precycle is only 32.35% while in the first cycle it reaches 67.65% means there is an increase of 35.30%, and in cycle II it increased to 85.29%, meaning there was an increase of 17.64%.